New Zealand's Exchange Rate Cycles: Evidence and Drivers - Gemma Mabin (New Zealand Government, The Treasury, 2010)
This paper seeks to understand the extent of New Zealand's exchange rate fluctuations compared to others, and what drives New Zealand's exchange rate. New Zealand has only experienced a limited number of exchange rate cycles since the dollar was floated. On a trade-weighted basis this paper finds that New Zealand has large exchange rate cycles, but that some other relevant economies (e.g. Australia, the Euro Area, Japan and South Korea) also have similarly large cycles. By comparing the short-term (i.e. month-to-month) volatility of New Zealand's exchange rate to other economies, on a trade-weighted basis New Zealand's exchange rate fluctuates greatly. New Zealand, Australia and Japan face the highest levels of short-term volatility out of the economies included in the analysis. Factors that affect the expected relative return on New Zealand dollar assets are found to explain a significant part of exchange rate cycles. These include interest rate differentials between New Zealand and other countries, relative growth performance and attitudes to risk. More fundamental drivers such as export commodity prices and the terms of trade, and productivity growth also drive New Zealand dollar returns. The main driver of the exchange rate changes over time in response to developments in the domestic and global economy.
Keywords: F31; 330; Exchange rate; short-term volatility; medium-term cycles; long-run equilibrium; Wechselkurspolitik; Wechselkurs; Volatilität; Konjunkturstatistik; Neuseeland